2021
DOI: 10.3390/jcm10245738
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interval between Recurrence and Reinjection in Anti-VEGF Therapy for Diabetic Macular Edema in Pro Re Nata Regimen

Abstract: Background: Pro re nata (PRN) regimen using anti-vascular endothelial growth factor (VEGF) agent is popular for the treatment of diabetic macular edema (DME). We investigated the influence of waiting time (WT) and interval between the date of recurrence of edema and re-injection on treatment efficacy. Methods: This retrospective study conducted at 7 sites in Japan enrolled patients who received intravitreal injection of ranibizumab (IVR) and aflibercept (IVA) in 1+PRN regimen. Enrolled patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Moreover, the number of patients injected more than five times was less than 6.0%. For recurrent edema, the prognosis for vision is poor if injections are not administered promptly; thus, administering a sufficient number of injections is recommended 21 . Although frequent injections increase the economic burden on patients 22 , new anti‐VEGF agents such as brolucizumab and faricimab have been developed for diabetic macular edema, and regimens with longer dosing intervals have been proposed 23 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of patients injected more than five times was less than 6.0%. For recurrent edema, the prognosis for vision is poor if injections are not administered promptly; thus, administering a sufficient number of injections is recommended 21 . Although frequent injections increase the economic burden on patients 22 , new anti‐VEGF agents such as brolucizumab and faricimab have been developed for diabetic macular edema, and regimens with longer dosing intervals have been proposed 23 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey of Japanese retinal specialists, the most common anti-VEGF treatment regimen is PRN, which involves injection at each recurrence [7,18]. However, delayed injection timing for DME recurrence has been reported to worsen visual prognosis [11]. Moreover, an increase in drop-offs and interruptions in ophthalmology visits are associated with worse visual prognosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Matsunaga et al showed that anti-VEGF-treated patients who were lost to follow-up for a prolonged period experienced a modest decline in visual acuity, which recovered after restarting injections [10]. In addition, we recently reported that better visual improvement cannot be achieved without prompt injection once edema recurrence has been identified [11]. Therefore, it is clinically important to monitor the status of DME through regular visits to ophthalmologists, and to administer anti-VEGF agents at the appropriate time.…”
Section: Introductionmentioning
confidence: 98%
“…Intravitreal injections were performed in a standard manner by a trained ophthalmologist using 0.4% oxybuprocaine hydrochloride (0.4% benoxyl ophthalmic solution, Santen Co. Ltd., Osaka, Japan) and 2% xylocaine as anesthetic, and povidone iodine for sterilization. The injection volume of ranibizumab (Lucentis; Novoartis Pharma K.K., Tokyo, Japan) and aflibercept (Eylea; Bayer Yakuhin, Ltd., Tokyo, Japan) was 0.5 mg/0.05 mL and 2 mg/0.05 mL, respectively [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, two VEGF inhibitors, aflibercept and ranibizumab, have been approved for the treatment of DME by injection into the vitreous cavity. However, multiple injections are required to maintain the therapeutic effect, having an economic burden on the patient and the healthcare system due to the expense of the drug [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%